IL-15 Upregulates Telomerase Expression and Potently Increases Proliferative Capacity of NK, NKT-Like, and CD8 T Cells - Watkinson, Fiona; Nayar, Sandeep Krishan; Rani, Aradhana; Sakellariou, Christina A.; Elhage, Oussama; Papaevangelou, Efthymia; Dasgupta, Prokar; Galustian, Christine (Frontiers in Immunology, 2021)
Interleukin-15 (IL-15) is a cytokine that has been shown to expand CD8 T cell and natural killer (NK) cell populations, and therefore has potential for potentiating adoptive immune cell therapy for cancer. Previously, IL-15 has been shown to induce proliferation of CD8 memory T cells through activation of telomerase. Here, we investigated whether telomerase is also activated during the IL-15 mediated proliferation of NK and NKT-like (CD56+CD3+) cells. We also examined the extent that each of the three signaling pathways known to be stimulated by IL-2/IL-15 (JAK-STAT, PI3K-AKT Ras-RAF/MAPK) were activated and involved in the telomerase expression in the three cell types NK, NKT or CD8 T cells. To assess cell proliferation and doubling, peripheral blood mononuclear cells (PBMCs) or isolated NK, NKT-like or CD8 T cells were incubated with varying concentrations of IL-15 or IL-2 for 7 days. CD8 T, NK and NKT cell expansion was determined by fluorophore-conjugated antibody staining and flow cytometry. Cell doubling was investigated using carboxyfluorescein-succinimidyl-ester (CFSE). Telomerase expression was investigated by staining cells with anti-telomerase reverse transcriptase (anti-TERT). Telomerase activity in CD56+ and CD8 T cells was also measured via Telomerase Repeat Amplification Protocol (TRAP). Analysis of cellular expansion, proliferation and TERT expression concluded that IL-15 increased cellular growth of NK, NKT and CD8 T cells more effectively than IL-2 using low or high doses. IL-15, increased TERT expression in NK and NKT cells by up to 2.5 fold, the same increase seen in CD8 T cells. IL-2 had effects on TERT expression only at high doses (100-1000 ng/ml). Proteome profiling identified that IL-15 activated selected signaling proteins in the three pathways (JAK-STAT, PI3K-AKT, Ras-MAPK) known to mediate IL-2/IL-15 signaling, more strongly than IL-2. Evaluation by signaling pathway inhibitors revealed that JAK/STAT and PI3K/AKT pathways are important in IL-15’s ability to upregulate TERT expression in NK and NKT cells, whereas all three pathways were involved in CD8 T cell TERT expression. In conclusion, this study shows that IL-15 potently stimulates TERT upregulation in NK and NKT cells in addition to CD8 T cells and is therefore a valuable tool for adoptive cell therapies.